Prognostic assessment of sarcopenia in patients with fractures: a systematic review and meta-analysis - Hejie Zheng; Tianhong Wang; Zhuoyang Li; Huimin Lu (BMC Musculoskeletal Disorders)
Abstract Background Currently, the prevalence of sarcopenia is on the rise. Sarcopenia may significantly affect the prognosis of fracture patients by increasing postoperative complications, diminishing quality of life, and raising mortality rates. This studyaims to investigate the impact of sarcopenia on the prognosis of fractures. Methods A systematic search was carried out in PubMed, Embase, Cochrane Library, and Web of Science using the keywords “sarcopenia” and “fracture” from the inception of each database to January 14, 2025. The logarithm and its standard error of the odds ratio (OR) were calculated to assess the effect size. Sensitivity analysis was conducted using a one-by-one exclusion approach. Publication bias was evaluated through funnel plots, Egger’s test, Begg’s test, and the trim and fill method. Results Our pooled analysis of data from 30 studies, comprising 32 datasets, demonstrated that sarcopenia significantly elevated the risk of poor prognosis in fracture patients (OR 1.51, 95% CI 1.24–1.85), particularly, the risk of refracture (OR 1.66, 95% CI 1.36–2.03). In hip fractures, sarcopenia similarly increased the risk of poor prognosis (OR 1.43, 95% CI 1.17–1.76), refracture (OR 1.54, 95% CI 1.21–1.96) and poor functional recovery (OR 2.13, 95% CI 1.41–3.21). Conclusion Sarcopenia plays a crucial role as a risk factor for poor prognosis in patients with fractures, including both an elevated risk of mortality, refracture and poor functional recovery. This necessitates that clinical workers place greater emphasis on the identification and diagnosis of sarcopenia in practice, deliver enhanced clinical care tailored to fracture patients, conduct more prospective studies, and advocate for the global standardization of sarcopenia diagnostic criteria in the future.